Kombinasi Alat Cardiac Contractility Modulation dan Terapi Sel Punca Hematopoetik CD34+CD133+ sebagai Terapi Gagal Jantung dengan Penurunan Fraksi Ejeksi - Ridwan, Alifaturrasyid Syafatullah; Suryoadji, Kemal Akbar (Cermin Dunia Kedokteran, 2022)
Gagal jantung merupakan penyebab morbiditas dan mortalitas di seluruh dunia dan di Indonesia. Seiring progresi penurunan fungsi kontraktilitas jantung, terapi farmakologis seringkali tidak cukup, sehingga terapi invasif seperti cardiac contractility modulation (CCM) merupakan alternatif. Terapi regeneratif dengan sel punca dewasa CD34+CD133+ juga menunjukkan manfaat memperbaiki perfusi miokard dan inhibisi kerusakan lanjut pasca-iskemia. Studi literatur ini mengevaluasi potensi gabungan modalitas terapi listrik CCM dengan terapi regeneratif sel progenitor CD34+CD133+ pada pasien gagal jantung kronis dengan penurunan fraksi ejeksi hingga <30% berdasarkan penelitian 10 tahun terakhir di database online PubMed, Scopus, dan EBSCO. Kombinasi CCM dengan infus sel punca terbukti meningkatkan kontraktilitas dan membatasi area fibrosis pasca-infark. Dapat disimpulkan bahwa terapi CCM untuk perbaikan kontraktilitas berpotensi dikombinasikan dengan terapi regeneratif sel punca CD34+CD133+ untuk memaksimalkan perbaikan kontraktilitas jantung pada pasien gagal jantung kronis dengan penurunan fraksi ejeksi berat. Heart failure is the leading cause of morbidity and mortality in general population both worldwide and in Indonesia. The progression of decreased cardiac contractility may result in inadequate pharmacological therapy, and invasive therapy such as cardiac contractility modulation (CCM) is an alternative. Regenerative therapy with adult stem cells CD34+CD133+ in various studies has also shown benefits for improving myocardial perfusion and inhibition of further post-ischemic damage. This literature study aims to evaluate the potential of combined cardiac contractility modulation (CCM) electric therapy and CD34+CD133+ progenitor cells regenerative therapy in chronic heart failure with a reduced ejection fraction to <30%. The literature study was compiled from studies of the last 10 years and registered in the online database of PubMed, Scopus, and EBSCO. This study found CCM can increase natural contraction of myocardium without increasing oxygen demand and also influences remodeling myocardium to increase its ejection fraction. Various clinical trials have also shown subpopulations of CD34+CD133+ progenitor cells from bone marrow play a role in enhancing perfusion in post-infarct myocardium, inducing myocardial repopulation and inhibiting further damage to ischemic myocardium. The combination of CCM with cell infusion has been shown to increase contractility and limit the area of post-infarct fibrosis. CCM and regenerative therapy with stem cells CD34+CD133+ may be potentially combined to maximize therapeutic cardiac contractility improvement in chronic heart failure patients with severe reduction of ejection fraction.